KNOWLEDGE, ATTITUDES, AND PRACTICES ASSOCIATED WITH ACCESS TO SANITATION IN OPEN PUBLIC PLACES - A CASE OF NAIROBI CITY. - Odongo, Beverlyne (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Improving the uptake of existing sanitation facilities in Nairobi CBD requires a change in behavioral practices of the population. In this study we analyzed knowledge, attitudes and practices associated with sanitation access to open public spaces in Nairobi city. The study objectives were to identify knowledge gaps associated with access to public sanitation in Nairobi city as there’s a significant lack of knowledge on the importance of proper hygiene. Assessing the attitudes, habits and behavior associated with access to public sanitation and determining sanitation practices in women of Nairobi central business district as social stigma and cultural beliefs discourage the use of public toilets especially among women and children. A descriptive quantitative cross-sectional study design was employed to obtain data from the participants. Data was collected using structured open-ended questionnaires, interviews and spot checks and analyzed using SPSS V29. The findings indicated that many of the respondents 76.5% agree that sanitation is very important with 89.3% confirming to having used public toilets in the city. Daily use was low at 6.7% with 89.3% indicating that the facilities were inadequate leading to open defecation and environmental degradation. Accessibility was the most influencing factor for use of sanitation facilities even though a majority 39.3% were dissatisfied with the conditions of the public toilets depicting the perception that public toilets are unhygienic and unsafe. Additionally, 88.9% agreed to paying to use the toilet facilities highlighting the importance of willingness to pay for environmental services. The study recommends for Proper maintenance of existing sanitation facilities to improve on accessibility and the quality-of-service delivery coupled with targeted educational campaigns on sanitation and hygiene.